-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy patharith-sum-formula.agda
265 lines (256 loc) · 8.14 KB
/
arith-sum-formula.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
--https://www.codewars.com/kata/5c8b332197eb04000887fd63
open import Relation.Binary.PropositionalEquality using (refl; _≡_; cong; sym)
open Relation.Binary.PropositionalEquality.≡-Reasoning using (begin_; step-≡; _∎; _≡⟨⟩_)
open import Data.Nat.Base
open import Data.Nat.Properties using (+-comm; +-identityʳ; +-assoc)
open import Data.Nat.Solver
open Data.Nat.Solver.+-*-Solver
arith-sum : ℕ → ℕ
arith-sum zero = zero
arith-sum n'@(suc n) = n' + arith-sum n
arith-formula : ℕ → ℕ
arith-formula n = ⌊ n * (n + 1) /2⌋
n+1=suc_n : {n : ℕ} → n + 1 ≡ suc n
n+1=suc_n {zero} = refl
n+1=suc_n {suc n} = cong suc ( n+1=suc_n {n})
l2 : {n m : ℕ} → n * (m + 1) ≡ (n * m) + n
l2 {zero} {m} = refl
l2 {suc n} {m} =
begin
m + 1 + n * (m + 1)
≡⟨ cong (λ x → m + 1 + x) (l2 {n} {m}) ⟩
m + 1 + (n * m + n)
≡⟨ +-comm (m + 1) (n * m + n) ⟩
(n * m + n) + (m + 1)
≡⟨ refl ⟩
n * m + n + (m + 1)
≡⟨ +-assoc (n * m) n (m + 1) ⟩
n * m + (n + (m + 1))
≡⟨ cong (λ x → n * m + x) (sym (+-assoc n m 1)) ⟩
n * m + (n + m + 1)
≡⟨ cong (λ x → n * m + (x + 1)) (+-comm n m) ⟩
n * m + (m + n + 1)
≡⟨ cong (λ x → x) (sym (+-assoc (n * m) (m + n) 1)) ⟩
n * m + (m + n) + 1
≡⟨ cong (λ x → x + 1) (sym (+-assoc (n * m) m n)) ⟩
n * m + m + n + 1
≡⟨ cong (λ x → x + n + 1) (sym (+-comm m (n * m))) ⟩
m + n * m + n + 1
≡⟨ +-assoc (m + n * m) n 1 ⟩
m + n * m + (n + 1)
≡⟨ cong (λ x → m + n * m + x) (n+1=suc_n {n}) ⟩
m + n * m + suc n
∎
where
lemma3 : {a b c d : ℕ} → a + b + c + d ≡ a + (b + c) + d
lemma3 {a} {b} {c} {d} = cong (λ x → x + d) (+-assoc a b c)
arith-eq : (n : ℕ) -> arith-formula n ≡ arith-sum n
arith-eq zero = refl
arith-eq (suc zero) = refl
arith-eq n'@(suc n) = --{!!}
begin
arith-formula (suc n)
≡⟨ refl ⟩
⌊ suc n * (suc n + 1) /2⌋
≡⟨ cong (λ x → ⌊ suc n * x /2⌋) n+1=suc_n ⟩
⌊ suc n * (suc (suc n)) /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋) (lemma1 {suc n}) ⟩
⌊ suc n + suc n * suc n /2⌋
≡⟨ cong (λ x → ⌊ suc n + x /2⌋ ) (lemma2 {n}) ⟩
⌊ suc n + suc (n * n + 2 * n) /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋) (lemma3) ⟩
⌊ suc ( suc (n + (n * n + 2 * n))) /2⌋
≡⟨ refl ⟩
suc ⌊ n + (n * n + 2 * n) /2⌋
≡⟨
cong suc (
begin
⌊ n + (n * n + 2 * n) /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋) (sym (+-assoc n (n * n) (n + (n + zero)))) ⟩
⌊ n + n * n + 2 * n /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋) (solve 1 (λ n → n :+ n :* n :+ con 2 :* n := con 2 :* n :+ (n :+ n :* n)) refl n) ⟩
⌊ 2 * n + (n + n * n) /2⌋
≡⟨ lemma5 {n} ⟩
n + ⌊ (n + n * n) /2⌋
≡⟨
cong (n +_) (
begin
⌊ n + n * n /2⌋
≡⟨ lemma6 {n} ⟩
arith-sum n
∎
)
⟩
n + arith-sum n
∎
)
⟩
suc n + arith-sum n
∎
where
lemma1 : {a b : ℕ} → a * (suc b) ≡ a + a * b
lemma1 {zero} {b} = refl
lemma1 {suc a} {b} = cong suc (
begin
b + a * suc b
≡⟨ cong (λ x → b + a * x) (sym n+1=suc_n) ⟩
b + a * (b + 1)
≡⟨ cong (λ x → b + x) (l2 {a} {b}) ⟩
b + (a * b + a)
≡⟨ cong (λ x → b + x) (+-comm (a * b) a) ⟩
b + (a + (a * b))
≡⟨ sym (+-assoc b a (a * b)) ⟩
(b + a) + (a * b)
≡⟨ cong (λ x → x + a * b) (+-comm b a) ⟩
a + b + a * b
≡⟨ +-assoc a b (a * b) ⟩
a + (b + a * b)
∎
)
lemma2 : {n : ℕ} → suc n * suc n ≡ suc (n * n + 2 * n)
lemma2 {zero} = refl
lemma2 {suc n}
rewrite +-assoc n (n * suc n) (suc (n + suc (n + zero))) =
cong suc (cong suc (
cong (n +_) (
begin
suc (suc (n + n * suc (suc n)))
≡⟨ cong (λ x → suc (suc (n + x))) (lemma1 {n}) ⟩
suc (suc (n + (n + n * suc n)))
≡⟨ cong (λ x → suc (suc (n + (n + n * x)))) ll2 ⟩
suc (suc (n + (n + n * (n + 1))))
≡⟨ cong (λ x → suc (suc (n + (n + (x))))) (l2 {n}) ⟩
suc (suc (n + (n + (n * n + n))))
≡⟨ refl ⟩
suc (suc n + (n + (n * n + n)))
≡⟨ refl ⟩
suc (suc n) + (n + (n * n + n))
≡⟨ cong (λ x → suc x + (n + (n * n + n))) (ll2 {n}) ⟩
suc (n + 1 + (n + (n * n + n)))
≡⟨ cong (λ x → x + 1 + (n + (n * n + n))) (ll2 {n}) ⟩
n + 1 + 1 + (n + (n * n + n))
≡⟨ solve 1 (λ n → n :+ con 1 :+ con 1 :+ (n :+ (n :* n :+ n))
:= (n :+ n :* n) :+ (n :+ con 1 :+ (n :+ con 1))) refl n ⟩
(n + n * n) + (n + 1 + (n + 1))
≡⟨ cong (λ x → (n + n * n) + (n + 1 + x)) (sym (ll2 {n})) ⟩
(n + n * n) + (n + 1 + suc n)
≡⟨ cong (λ x → (n + n * n) + (x + suc n)) (sym (ll2 {n})) ⟩
(n + n * n) + (suc n + suc n)
≡⟨ refl ⟩
(n + n * n) + suc (n + suc n)
≡⟨ cong (λ x → x + suc (n + suc n)) (sym (lemma1 {n})) ⟩
n * suc n + suc (n + suc n)
≡⟨ cong (λ x → n * suc n + suc (n + suc x) ) (sym ll1) ⟩
n * suc n + suc (n + suc (n + zero))
∎
)
)
)
where
ll1 : {n' : ℕ} → n' + zero ≡ n'
ll1 {zero} = refl
ll1 {suc n'} = cong suc (ll1 {n'})
ll2 : {a : ℕ} → suc a ≡ a + 1
ll2 {zero} = refl
ll2 {suc a} = cong suc ll2
lemma3 : {n m : ℕ} → suc n + suc m ≡ suc (suc (n + m))
lemma3 {zero} {m} = refl
lemma3 {suc n} {m} = cong suc ( cong suc n+suc_m≡suc_n+m)
where
n+suc_m≡suc_n+m : {n m : ℕ} → n + suc m ≡ suc (n + m)
n+suc_m≡suc_n+m {zero} {m} = refl
n+suc_m≡suc_n+m {suc n} {m} = cong suc n+suc_m≡suc_n+m
n+n=2*n : ∀ {n} → n + n ≡ 2 * n
n+n=2*n {zero} = refl
n+n=2*n {suc n} rewrite (+-identityʳ n) = cong suc refl
lemma4 : {n : ℕ} → ⌊ 2 * n /2⌋ ≡ n
lemma4 {zero} = refl
lemma4 {suc n} = --{!!}
begin
⌊ suc (n + suc (n + zero)) /2⌋
≡⟨ cong (λ x → ⌊ suc n + suc x /2⌋) (+-identityʳ n ) ⟩
⌊ suc (n + suc n) /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋) lemma3 ⟩
⌊ suc ( suc (n + n)) /2⌋
≡⟨ refl ⟩
suc ⌊ n + n /2⌋
≡⟨
cong suc (
begin
⌊ n + n /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋) (n+n=2*n {n}) ⟩
⌊ 2 * n /2⌋
≡⟨ lemma4 ⟩
n
∎
)
⟩
suc n
∎
lemma5 : {n m : ℕ} → ⌊ 2 * n + m /2⌋ ≡ n + ⌊ m /2⌋
lemma5 {zero} {m} = refl
lemma5 {suc n} {m} rewrite (+-identityʳ n) =
begin
⌊ suc (n + suc n + m) /2⌋
≡⟨ refl ⟩
⌊ suc (n + suc n) + m /2⌋
≡⟨ cong (λ x → ⌊ x + m /2⌋) lemma3 ⟩
⌊ suc (suc (n + n)) + m /2⌋
≡⟨ refl ⟩
suc ⌊ (n + n) + m /2⌋
≡⟨
cong suc (
begin
⌊ n + n + m /2⌋
≡⟨ cong (λ x → ⌊ x + m /2⌋ ) (n+n=2*n {n} )⟩
⌊ 2 * n + m /2⌋
≡⟨ lemma5 {n} {m} ⟩
n + ⌊ m /2⌋
∎
)
⟩
suc (n + ⌊ m /2⌋)
∎
lemma6 : {n : ℕ} → ⌊ n + n * n /2⌋ ≡ arith-sum n
lemma6 {zero} = refl
lemma6 {suc n} =
begin
⌊ suc (n + suc (n + n * suc n)) /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋ ) (lemma3 {n}) ⟩
⌊ suc ( suc (n + (n + n * suc n))) /2⌋
≡⟨ refl ⟩
suc ⌊ n + (n + n * suc n) /2⌋
≡⟨
cong suc (
begin
⌊ n + (n + n * suc n) /2⌋
≡⟨ cong (λ x → ⌊ n + (n + n * x) /2⌋) (sym (n+1=suc_n)) ⟩
⌊ n + (n + n * (n + 1)) /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋)
(solve 1 (λ n →
n :+ (n :+ n :* (n :+ con 1)) :=
con 2 :* n :+ n :* (n :+ con 1)
)
refl n) ⟩
⌊ 2 * n + n * (n + 1) /2⌋
≡⟨ lemma5 {n} ⟩
n + ⌊ n * (n + 1) /2⌋
≡⟨
cong (n +_) (
begin
⌊ n * (n + 1) /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋ ) (l2 {n}) ⟩
⌊ n * n + n /2⌋
≡⟨ cong (λ x → ⌊ x /2⌋) (+-comm (n * n) n) ⟩
⌊ n + n * n /2⌋
≡⟨ lemma6 {n} ⟩
arith-sum n
∎
)
⟩
n + arith-sum n
∎
)
⟩
suc (n + arith-sum n)
∎